Matching the 'knowing what to do' and the 'doing what you know' in ethical decision-making - Chang Yuan Loh; Jin Boon Wong (Australasian Accounting, Business and Finance Journal, 2009)
Corporate events in the past decades have contributed to a continued interest in the ethical decision-making of individuals in accounting. Much of the research in ethics and education have relied on the assumption that the individual’s level of ethical development is related to his/her ethical behavior. Adapting a simplified version of Thorne’s (2000) prescriptive/deliberative reasoning in a cheat-to-gain business scenario, a survey of accounting students suggest that ethical development may not be related to behavior. In addition, consistent with Thorne (2001), results suggest that even if individuals may ‘know what to do’ for the ideal ethical decision, they may not always actually choose that path or ‘doing what they know’.